Monitoring of mycophenolic acid in the plasma of transplant patients by capillary electrophoresis - (:unkn) unknown (SPRINGER HEIDELBERG, 2006)
Plasma samples from 60 transplant patients on mycophenolate mofetil therapy were analysed using validated capillary electrophoresis (CE) method to determine mycophenolic acid (MPA) and its main metabolite mycophenolic acid glucuronide. Enzyme multiplied immunoassay technique (EMIT) values were available for the same samples. The differences between the results from the two methods was clarified by using Bland-Altman analysis and further statistical analysis. More than 90% of the results showed a positive bias, with EMIT giving higher levels than CE.
Keywords: capillary electrophoresis; enzyme multiplied immunoossay; mycophenolic acid; TANDEM MASS-SPECTROMETRY; LIQUID-CHROMATOGRAPHY; GLUCURONIDE METABOLITE; RECIPIENTS; MOFETIL; EMIT; IMMUNOASSAY; HPLC; PHARMACOKINETICS; IDENTIFICATION